Clinical and electrophysiological characteristics of women with X‐linked Charcot–Marie–Tooth disease - Barbat du Closel, Luce; Bonello‐Palot, Nathalie; Péréon, Yann; Echaniz‐Laguna, Andoni; Camdessanche, Jean Philippe; Nadaj‐Pakleza, Aleksandra; Chanson, Jean‐Baptiste; Frachet, Simon; Magy, Laurent; Cassereau, Julien; Cintas, Pascal; Choumert, Ariane; et al. (European journal of neurology, 2023)
X-Linked Charcot-Marie-Tooth disease type 1 (CMTX1) is characterized by gender differences in clinical severity. Women are usually clinically affected later and less severely than men. However, their clinical presentation appears to be heterogenous. Our aim was to extend the phenotypic description in a large series of women with CMTX1. We retrospectively evaluated 263 patients with CMTX1 from 11 French reference centers. Demographic, clinical, and nerve conduction data were collected. The severity was assessed by CMT Examination Score (CMTES) and Overall Neuropathy Limitations Scale (ONLS) scores. We looked for asymmetrical strength, heterogeneous motor nerve conduction velocity (MNCV), and motor conduction blocks (CB). The study included 137 women and 126 men from 151 families. Women had significantly more asymmetric motor deficits and MNCV than men. Women with an age of onset after 19 years were milder. Two groups of women were identified after 48 years of age. The first group represented 55%, with women progressing as severely as men, however, with a later onset age. The second group had mild or no symptoms. Some 39% of women had motor CB. Four women received intravenous immunoglobulin before being diagnosed with CMTX1. We identified two subgroups of women with CMTX1 who were over 48 years of age. Additionally, we have demonstrated that women with CMTX can exhibit an atypical clinical presentation, which may result in misdiagnosis. Therefore, in women presenting with chronic neuropathy, the presence of clinical asymmetry, heterogeneous MNCV, and/or motor CB should raise suspicion for X-linked CMT, particularly CMTX1, and be included in the differential diagnosis.